Chemiplasmonics for high-throughput biosensors - Raghavendra AJ (Dove Medical Press, 2018)
Achyut J Raghavendra,1,* Jingyi Zhu,1,* Wren Gregory,1 Fengjiao Case,1 Pradyumna Mulpur,2 Shahzad Khan,3 Anurag Srivastava,3 Ramakrishna Podila1 1Laboratory of Nano-biophysics, Clemson University, Clemson, SC 29634, USA; 2Clemson Nanomaterials Institute, Clemson University, Anderson, SC 29625, USA; 3ABV-Indian Institute of Information Technology and Management, Gwalior, MP, India *These authors contributed equally to this work Background: The sensitivity of ELISA for biomarker detection can be significantly increased by integrating fluorescence with plasmonics. In surface-plasmon-coupled emission, the fluorophore emission is generally enhanced through the so-called physical mechanism due to an increase in the local electric field. Despite its fairly high enhancement factors, the use of surface-plasmon-coupled emission for high-throughput and point-of-care applications is still hampered due to the need for expensive focusing optics and spectrometers.Methods: Here, we describe a new chemiplasmonic-sensing paradigm for enhanced emission through the molecular interactions between aromatic dyes and C60 films on Ag substrates.Results: A 20-fold enhancement in the emission from rhodamine B-labeled biomolecules can be readily elicited without quenching its red color emission. As a proof of concept, we demonstrate two model bioassays using: 1) the RhB–streptavidin and biotin complexes in which the dye was excited using an inexpensive laser pointer and the ensuing enhanced emission was recorded by a smartphone camera without the need for focusing optics and 2) high-throughput 96-well plate assay for a model antigen (rabbit immunoglobulin) that showed detection sensitivity as low as 6.6 pM.Conclusion: Our results show clear evidence that chemiplasmonic sensors can be extended to detect biomarkers in a point-of-care setting through a smartphone in simple normal incidence geometry without the need for focusing optics. Furthermore, chemiplasmonic sensors also facilitate high-throughput screening of biomarkers in the conventional 96-well plate format with 10–20 times higher sensitivity. Keywords: biosensor, surface plasmons, nanosilver, fluorescence, fullerenes